Product-focused software process improvement : 17th International Conference, PROFES 2016, Trondheim, Norway, November 22-24, 2016, Proceedings /: 17th International Conference, PROFES 2016, Trondheim, Norway, November 22-24, 2016, Proceedings. (2016) - Unknown
No abstract available